Cumulation and acceleration of ions by TW femtosecond laser pulse - Balakirev, V.A.; Dovbnya, A.N.; Yegorov, A.M.; Krasnogolovets, M.A.; Onishchenko, I.N.; Onishchenko, N.I.; Povrozin, A.I.; Pristupa, V.I. (Вопросы атомной науки и техники, 2004)
A new method of ion cumulation and acceleration at three-dimensional compression of plasma in the ”light trap” created in the focal region of the high-power femtosecond laser is theoretically studied. The ”light trap” is formed by delay in time of the central part of the laser pulse being focused. The cumulation degree and maximum energy of acceleration ions depending on values of the high-power femtosecond laser pulse have been investigated by numerical methods. Physical mechanisms of ion density and energy increase in the paraxial plasma zone have been discussed. The proposed method of ion cumulation and acceleration allows one to create compact bright sources of fast neutrons, nuclei for x-ray and gamma lasers, and also provides the unique possibilities of nuclear reaction initiation and isotope production.